2019
DOI: 10.1088/1361-6544/ab159b
|View full text |Cite
|
Sign up to set email alerts
|

Global boundedness and decay property of a three-dimensional Keller–Segel–Stokes system modeling coral fertilization

Abstract: This paper is concerned with the four-component Keller-Segel-Stokes system modelling the fertilization process of corals:subject to the boundary conditions ∇c · ν = ∇m · ν = (∇ρ − ρS(x, ρ, c)∇c) · ν = 0 and u = 0, and suitably regular initial data⊂ R 3 is a bounded domain with smooth boundary ∂Ω. This system describes the spatiotemporal dynamics of the population densities of sperm ρ and egg m under a chemotactic 1 process facilitated by a chemical signal released by the egg with concentration c in a fluidflow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…It is noted that a similar result was proved in [18] for the three-dimensional Stoke variant of (1.4). However, as is well-known, the nonlinear convection (u • ∇)u in the three-dimensional Navier-Stokes equation may enforce the spontaneous emergence of singularities in the sense of blow-up with respect to the norm in L ∞ (Ω), we thereby subject the study of classical solutions of (1.4) to small initial data by an essentially one-step contradiction argument, unlike that in the two-dimensional case ( [9]).…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…It is noted that a similar result was proved in [18] for the three-dimensional Stoke variant of (1.4). However, as is well-known, the nonlinear convection (u • ∇)u in the three-dimensional Navier-Stokes equation may enforce the spontaneous emergence of singularities in the sense of blow-up with respect to the norm in L ∞ (Ω), we thereby subject the study of classical solutions of (1.4) to small initial data by an essentially one-step contradiction argument, unlike that in the two-dimensional case ( [9]).…”
Section: Introductionsupporting
confidence: 73%
“…Although the proof of Lemma 3.2 and Lemma 3.3 below is very similar to that of Lemma 3.11 and Lemma 3.12 in [18], respectively, we give their proofs for the convenience of the interested reader.…”
Section: Preliminariesmentioning
confidence: 99%
“…For example, Chae, Kyungkeun, and Lee [9] studied the global well-posedness of coral fertilization models. Li, Pang, and Wang [10] explored the global boundedness and decay property. Zheng [11] showed the global weak solution of this system in a three-dimensional space.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Specially, in spatially two-dimensional setting, it is proved that system (1.1) with κ = 1 possesses a unique classical solution which is globally bounded and approaches to some constant equilibrium as time goes to infinity ( [14]). While for physically most relevant three-dimensional case, the corresponding global solvability of (1.1) in the context of Stokes-fluid or Navier-Stokes-fluid requires some smallness hypothesis for initial data ( [22,27,7,18]), or necessary aids of some type of nonlinear mechanism, such as porous medium diffusion ( [26]), or signal-dependent sensitivity ( [21]), or saturation effects of cells ( [22,18,24,38]), or p-Laplace diffusion of cells ( [25]). Recently, from some refined models proposed in [1,5,6], it can be observed that the migration of cells rests with some gradient-dependent limitations, which inspires investigations of global dynamics on associated initial-boundary problems.…”
Section: Introductionmentioning
confidence: 99%